Exertional Leg Pain in Familial Mediterranean Fever: A Manifestation of an Underlying Enthesopathy and a Marker of More Severe Disease. Issue 11 (November 2014) - Eshed, Iris; Rosman, Yossi; Livneh, Avi; Kedem, Ron; Langevitz, Pnina; Ben‐Zvi, Ilan; Lidar, Merav
<x xml:space="preserve">Abstract</x> Objective Exertional leg pain is a characteristic musculoskeletal manifestation of familial Mediterranean fever (FMF). We aimed to define the frequency and characteristics of exertional leg pain in a large cohort of FMF patients and to evaluate for additional signs and symptoms of spondyloarthritis (SpA) in this patient population. Methods FMF patients were allocated into study or control groups based on the presence or absence of exertional leg pain. Randomly selected patients underwent magnetic resonance imaging (MRI) of the ankle as well as plain radiography of the sacroiliac joints. Results The prevalence of exertional leg pain among the 170 FMF patients included in the study was 58.2%. Patients with exertional leg pain had significantly more joint attacks (74.7% versus 40.8%; P < 0.0001), fever attacks (35.4% versus 15.5%; P = 0.004), and pleuritis attacks (48.5% versus 29.6%; P = 0.013) as well as more attacks per year. Elevations of inflammation markers were significantly more frequent among the study group (for the erythrocyte sedimentation rate, 44.4% of patients versus 21.1% of patients; P = 0.016) (for the C‐reactive protein level, 48.4% of patients versus 31.8% of patients; P = 0.013), and M694V homozygosity was more prevalent among the study group (45.5% versus 21.1%; P = 0.001). Signs compatible with enthesopathy on MRI were observed in 73.5% of patients in the study group and in 33.3% of patients in the control group (P = 0.046). Definite SpA was diagnosed in 41.2% of the patients in the study group compared to none of the controls (P = 0.07) (odds ratio 1.7 [95% confidence interval 1.2–2.3]). Conclusion Exertional leg pain is a common manifestation of FMF and is a marker of a more severe disease phenotype. Additionally, exertional leg pain is frequently associated with sacroiliitis and an underlying ankle enthesopathy and should therefore be considered a new feature of SpA.